Immigration and Economic Growth in the OECD Countries, 1986-2006 - Ekrame Boubtane; Jean-Christophe Dumont; Christophe Rault (Institute for the Study of Labor (IZA), 2014)
This paper offers a reappraisal of the impact of migration on economic growth for 22 OECD countries between 1986-2006 and relies on a unique data set we compiled that allows us to distinguish net migration of the native-born and foreign-born by skill level. Specifically, after introducing migration in an augmented Solow-Swan model, we estimate a dynamic panel model using a system of generalized method of moments (SYS-GMM) to deal with the risk of an endogeneity bias of the migration variables. Two important findings emerge from our analysis. First, there exists a positive impact of migrants' human capital on economic growth. And second, the contribution of immigrants to human capital accumulation tends to dominate the mechanical dilution effect while the net effect is fairly small. This conclusion holds even in countries with highly selective migration policies.
Keywords: C23; F22; J24; J61; O41; O47; 330; immigration; growth; human capital; generalized methods of moments